1986
DOI: 10.1109/tmag.1986.1064638
|View full text |Cite
|
Sign up to set email alerts
|

Electrode erosion in high current, high energy transient arcs

Abstract: Introduction Experimental Setup Results Acknowledgements 05 References 06 D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 12 publications
5
30
0
Order By: Relevance
“…It is well documented in the literature on air-gap discharges (Ref 12,13) that greater erosion occurs in the cathodes under unipolar discharges while bipolar discharges lead to similar erosion losses in both electrodes. A detailed discussion of the effects of material removal from the anode during pulsed discharges in water can be found in Ref 17, and a number of factors may be at play.…”
Section: Electrode Materials Testsmentioning
confidence: 91%
“…It is well documented in the literature on air-gap discharges (Ref 12,13) that greater erosion occurs in the cathodes under unipolar discharges while bipolar discharges lead to similar erosion losses in both electrodes. A detailed discussion of the effects of material removal from the anode during pulsed discharges in water can be found in Ref 17, and a number of factors may be at play.…”
Section: Electrode Materials Testsmentioning
confidence: 91%
“…Although the cathode surface was smooth, tiny graphite particles were attached on the periphery of the cathode surface. This phenomenon could be attributed to the graphite cannot melt but only be sublimated, during discharging in a gas switch, the graphite electrode surface was heated by the arc, the energy exchange on anode and cathode were different under high-current, high coulomb transfer operating conditions [14], and the energy input into the anode was larger than that into the cathode, leading to serious material removal on the anode and sputtering on the cathode during discharge. Although serious erosion was observed during discharge, stable self-breakdown voltage was obtained during the lifetime experiments, this indicated that the erosion was uniform and the tiny graphite particles had no effect on the performance of the gas switch.…”
Section: Erosion Characteristic Of the Graphite Electrodesmentioning
confidence: 99%
“…I n the intense arc mode, erosion of the cathode is quite high. This severe erosion has several causes: the increase in electrical power dissipated a t the cathode, the increased radiant energy from the anode, and the ablation of the cathode surface caused by the mechanical and thermal effects of an anode jet impinging upon the cathode [24]. I n the diffuse arc mode with no anode sputtering, erosion of the anode is zero.…”
Section: E L E C T R O D E E R O S I O Nmentioning
confidence: 99%
“…It is possible that the extra power compensates for increased losses by the arc column; or that, while the overall anode power density increases, the local peak power density decreases. However, recent work by DONALDSON et al [24] indicates that the most probable explanation is that the increased erosion a t the shorter gaps is not primarily an effect of direct electric power dissipation, but rather reflects the meclianical and thermal erosion produced by the impact of a powerful plnvnin jet (anode jet) on the surface of the electrode [25].…”
mentioning
confidence: 99%